Realization of biological potential of winter resistance and productivity of perspective tea variety forms in Adygea - L. V. Vavilova (Новые технологии, 2017)
The article presents the results of an estimation of winter resistance and influence of degree of damages of shoots and leaves on growth, development and productivity of tea plants in the subsequent vegetation. The interrelation of the physiological parameters of plants with the realization of biological potential of perspective sorts for further selection of species isolated from the gene pool of the Adygh branch of ARSRIHHC is analyzed.